Rural-urban comparison in prevalence of hypertension and its factors among adolescents of Sarawak, Malaysia : A cross-sectional study - Cheah, Whye Lian; Chang, Ching Thon; Helmy, Hazmi; Kho, Grace Woei Feng (Turkish Society of Public Health Specialists, 2020)
This paper reports a study of the prevalence of pre-hypertension and hypertension, and its associated factors among secondary school students in Sarawak. Methods:It was a cross-sectional study using a questionnaire, anthropometric and blood pressure measurement. Results: A total of 2461 secondary school children participated. The prevalence of pre-hypertension was 13.2%, stage 1 hypertension was 12.4% and stage 2 hypertension was 4.6%. The prevalence of overweightness and obesity was 24.3%, elevated waist circumference was 13.5, and overfat and obese was 6.7%. Based on the urban model, factors that were associated with pre-hypertension were age, gender, parent with history of hypertension, overweightness and obesity. At the hypertension level, only maleness, overweightness and obesity were found to be associated factors.